Benefits to employers train & hire people with disabilities - Ismail, Fadillah; Abdul Hamid, Nor Aziati; Abdul Kadir, Adibah; Raja Mohd Rasi, Raja Zuraidah; Alhosani, Adnan Ali Hassan Humaid (Penerbit Uthm, 2019)
People with disabilities are present in this society more than 600 million in worldwide. In the estimation of World Health Organisation and World Bank, there are over a billion people which are 15% of the global population have a disability in the year of 2011 (Thompson, 2017). According to the statistic of Social Welfare Department there are 443,541 people having disability have registered on October 2017 which have mentioned by Deputy Minister of Women, Family and Social Department Datuk Azizah Mohd Dun (The Sundaily, 2017). Recently the statistics of people with disability have increase to 468,520 which stated by the Department Social Welfare on 20th April 2018 (Manaf et el., 2018). However, this data may not incomplete because the registration of people with disability is not compulsory and the names of those who died are haven’t deleted in the main record.